(untitled) (EAAE Annual Conference Proceedings, 2023)
The authors discuss a pedagogical experiment that arises out of an ongoing Erasmus+ project titled “Socially Situated Architectural Pedagogies” or SArPe, which involves the Universities of Pavia, Istanbul, TU Delft and Malaga. SArPe project situates itself in between three areas of inquiry: critical/radical pedagogies (Colomina et al., 2022; Crysler, 1995; Dutton & Mann, 1996; Hooks, 2014); situated knowledge (Haraway, 1988; Rendell, 2020) and commons-oriented knowledge and pedagogy (Bourassa et al., 2017; Deamer, 2022; Korsgaard, 2019).